COMPLETE SYSTEMS OF WEBER - HERMITE FUNCTIONS - Rusev, Peter (Ann. Sofia Univ. Fac. Math. and Inf., 1991)
Let { D_ u(z) }_ u C be system of Weber - Hermite functions. It is proved that the system (*) is complete in the space L_2(-∞, + ∞) if 0 < ω < 4/3 and Re σ > -1/2. The completeness of Hermite functions (**) in the same space is a particular case (ω=1, σ=0)